Analysis of brain activity during configuration learning using magnetoencephalography - Denisova, E.V.; Poznyak, L.A.; Pultsina, K.I.; Tretyakova, V.D.; Chernyshev, B.V. (Èksperimentalʹnaâ psihologiâ, 2025)
Context and relevance. This study investigates the brain encoding of complex stimuli during configurational associative learning in humans. Behavior based on the perception of complex signals provides high adaptability of human activity. Yet, knowledge about the involvement of the cerebral cortex in binding stimulus elements into a perceived holistic configuration remains incomplete and contradictory. Methods and materials. We used four elemental stimuli of different modalities (two visual and two auditory), and two complex multimodal stimuli composed of the same elemental stimuli. Two stimuli (one complex and one elemental stimulus) were paired with negative reinforcement (electrocutaneous stimulation). The task of the subject was to press a button if they anticipated an electrocutaneous stimulation after the presentation of each stimulus: the stimuli were presented in a pseudo-random order. Twenty-nine volunteers took part in the study. Results. The results of the study showed that reinforcement of a complex stimulus was accompanied by a significant increase in the power of theta oscillations in response to that stimulus. In addition, it was found that encoding configural association engaged theta oscillations to a greater extent compared to elemental association. These effects were found in localizations over prefrontal cortex, left dorsolateral frontal regions, right temporal regions, and posterior parieto-occipital regions. Conclusions. We hypothesize that this phenomenon is not only a consequence of the involvement of the hippocampus in the encoding of a complex stimulus, but also indicates an active interaction between the hippocampus and associative areas of the neocortex during learning. Контекст и актуальность. Работа посвящена исследованию кодирования мозгом комплексных стимулов при конфигурационном ассоциативном научении у человека. Поведение, которое основано на восприятии комплексных сигналов, обеспечивает высокую адаптивность человеческой деятельности. При этом на настоящий момент знания об участии коры больших полушарий в связывании стимульных элементов в воспринимаемую целостную конфигурацию остаются неполными и противоречивыми. Методы и материалы. Мы использовали четыре элементных разной модальности (два зрительных и два слуховых) и два комплексных мультимодальных стимула, составленные из тех же элементных стимулов. Два стимула (один комплексный и один элементный) сочетали с отрицательным подкреплением (электрокожным раздражением). Задача испытуемого состояла в нажатии кнопки в случае возникновения у него ожидания электрокожного раздражения после предъявления каждого стимула: стимулы предъявлялись в псевдослучайном порядке. В исследовании приняли участие 29 добровольных участников. Результаты исследования показали, что подкрепление комплексного стимула сопровождается значимым увеличением мощности тета-осцилляций в ответ на этот стимул. Кроме того, выявлено, что кодирование конфигурационной ассоциации вовлекает тета-осцилляции в большей степени в сравнении с элементной ассоциацией. Эти эффекты выявлены в локализациях, указывающих на префронтальную кору, левые дорсолатеральные фронтальные области, правые височные области и теменно-затылочные области. Выводы. Мы предполагаем, что этот феномен не только является следствием вовлечения гиппокампа в кодирование комплексного стимула, но и свидетельствует об активном взаимодействии между гиппокампом и ассоциативными областями новой коры в процессе научения.